Pengaruh Produksi dan Konsumsi Terhadap Impor Beras Di Provinsi Jambi Tahun 2010-2016 - Silvia Rahayu (Universitas Batanghari, 2019)
This study aims to determine the effect of rice production and consumption on rice imports in Jambi Province in 2010-2016 simultaneously and partially and calculate the effect of rice production and consumption on rice imports in Jambi Province in 2010-2016 simultaneously and partially. The data used in this research is secondary data. Data was analyzed using multiple lienear regression analysis. The results showed that: There is a significant influence between the variables of rice production and consumption on rice imports in Jambi Province in 2010-2016 simultaneously, this is evidenced by the calculated F value> F table or significance value> α. The magnitude of the effect of rice production and consumption on rice imports in Jambi Province simultaneously is 82.2%, while the remaining 17.8% is explained by other variables not examined in this study There is a significant influence between the variables of rice production on rice imports in the Province Jambi, this can be seen from the count -t value of <-t table which is -3.206 <-2.132 or the significance value <α is 0.002 <0.05. The magnitude of the effect of the rice production variable on rice imports in Jambi Province is with the value of β1 = -2,940, meaning that if rice production increases by 1 ton, rice imports will decrease by -2,940 assuming the other variables are constant. There is a significant influence between rice consumption variables on rice imports in Jambi Province, this can be seen from the value of t count> t table which is 3.076> 2.132 or a significance value <α that is 0.004 <0.05. The magnitude of the influence of rice consumption variables on rice imports in Jambi Province is with the value of β1 = 3.024, meaning that if rice consumption increases by 1 ton, rice imports will increase by 3.024 assuming the other variables are constant.